1988
DOI: 10.1210/jcem-66-2-454
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Renin and Prorenin (Inactive Renin) in Diabetes Mellitus: Effects of Intravenous Furosemide*

Abstract: PRA, active renin, and prorenin were measured in 32 normotensive diabetic patients and 14 normal subjects of similar ages before and after iv injection of 40 mg furosemide. The majority of the diabetic patients had normal PRA and active renin levels before and after furosemide, but in 4 normal subjects and 5 diabetic patients PRA did not rise after furosemide treatment to at least 0.25 ng angiotensin I/(L.s) as previously found in 90% of normal subjects. Two thirds of the diabetic patients had higher plasma pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Other studies have found reciprocal changes in active and inactive renin in normal subjects during acute stimulation of the renin-angiotensin system, which suggests that active renin is derived from inactive renin. 25 BryerAsh et al 26 have recently reported that in some diabetic patients renal conversion of inactive renin to active renin may be impaired, which results in elevated inactive renin levels with reduced PRA levels. We actually found a direct relation between inactive renin and PRA levels in both the control and diabetic groups in response to dietary sodium and posture.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found reciprocal changes in active and inactive renin in normal subjects during acute stimulation of the renin-angiotensin system, which suggests that active renin is derived from inactive renin. 25 BryerAsh et al 26 have recently reported that in some diabetic patients renal conversion of inactive renin to active renin may be impaired, which results in elevated inactive renin levels with reduced PRA levels. We actually found a direct relation between inactive renin and PRA levels in both the control and diabetic groups in response to dietary sodium and posture.…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin II also increases Animal models suggest that both ACE and chymase/ chymase-like pathways contribute to angiotensin II synthe cellular expression of fibronectin [59]. However, in 415 Renin-Angiotensin-Aldosterone-Kinin System and CVD in DM tissue angiotensin II levels has previously been reported, [63][64][65][66] both in types I and II diabetes mellitus [68,69].…”
Section: Anatomicmentioning
confidence: 99%
“…Some diabetics manifest attenuated renin release in Plasma renin activity response to furosemide-induced volume depletion [64]. 12 months of diabetes [72].…”
Section: Anatomicmentioning
confidence: 99%
See 2 more Smart Citations